TELEPRESENCE TECHNOLOGIES AS A NEW ANTHROPOLOGICAL PLATFORM FOR EDUCATION DEVELOPMENT - Lyudmila M. Andryukhina (Образование и наука)
The aim of the study is to explore the ways for overcoming deformations of anthropological educational bases caused by total informatization. Applying the theoretical and empirical analysis methods, the author indicates the trend toward displacement and substitution of the human image in education, and significant deformation of anthropological educational bases, resulting from informatization of education. The research relates the above anthropological deformations to the first phase of informatization and the platform of ≪human-computer technologies≫, based on Cartesian paradigm or the ≪culture of meaning≫.Scientific novelty involves substantiating the necessary transition to the new informatization phase of education, based on the telepresence technology and creating the ≪culture of presence≫. Thereby through the media technologies, a real man can be engaged in the process of academic communications. In the future, it can expand to creative cooperation, joint research projects and creative design.Apart from the theoretical value, the research has its practical significance resulting from the new anthropological platform formation in education.